Analisis Perbandingan Hubungan Zakat dan Pajak di Indonesia, Malaysia, dan Brunei Darussalam - Famulia, Ledy (UIN Sunan Kalijaga, 2020)
Abstract: Muslim majority countries have set their own policies and strategies in the handling and management of zakat and taxes. Some countries may apply similar management by correlating between zakat and taxes, but several other countries may establish different models. This article examines the correlation and management models of zakat and tax in three Muslim majority countries in Southeast Asia: Indonesia, Malaysia and Brunei Darussalam. Using a normative juridical approach and comparative analysis, this study concludes that the management of zakat and taxes in Indonesia, Malaysia, and Brunei Darussalam shares many similarities, but also has some differences. In Indonesia, zakat is made deductible from taxable income, while in Malaysia the zakat policy is applied as a tax deduction. The management of zakat and taxes in Brunei Darussalam is regulated differently since the two are not considered related to each other. The different models of zakat and tax management in Indonesia, Malaysia, and Brunei Darussalam turned out to have a significant effect on zakat and tax revenue in the three countries. Abstrak: Negara-negara muslim memiliki kebijakan dan cara tersendiri dalam menangani dan mengelola hubungan antara zakat dan pajak. Beberapa negara memiliki kemiripan dalam mengelola hubungan zakat dan pajak, namun beberapa negara yang lain menggunakan model yang berbeda . Artikel ini mengkaji hubungan dan model pengelolaan zakat dan pajak di tiga negara, yakni Indonesia, Malaysia dan Brunei Darussalam. Penelitian ini menggunakan pendekatan yuridis normatif dengan analisis perbandingan. Dari kajian yang telah dilakukan diperoleh kesimpulan bahwa pengelolaan zakat dan pajak di Indonesia, Malaysia, dan Brunei Darussalam memiliki banyak kemiripan, namun juga terdapat beberapa perbedaan. Jika di Indonesia zakat dijadikan sebagai pengurang penghasilan kena pajak maka di Malaysia diterapkan kebijakan zakat sebagai pengurang pajak. Sedangkan di Brunei Darussalam, zakat dan pajak tidak terkait satu sama lain. Perbedaan model pengelolaan zakat dan pajak di tiga negara ini: Indonesia, Malaysia, dan Brunei Darussalam ternyata berpengaruh cukup signifikan terhadap peningkatan pemerolehan zakat dan pajak sekaligus.